Global atmospheric eﬀects on the gravity ﬁeld quantities - TENZER, Robert; VAJDA, Peter; HAMAYUN, K (Contributions to Geophysics and Geodesy, 2009)
We compile the global maps of atmospheric eﬀects on the gravity ﬁeld quantities using the spherical harmonic representation of the gravitational ﬁeld. A simple atmospheric density distribution is assumed within a lower atmosphere (< 6 km). Dis- regarding temporal and lateral atmospheric density variations, the radial atmospheric density model is deﬁned as a function of the nominal atmospheric density at the sea level and the height. For elevations above 6 km, the atmospheric density distribution from the United States Standard Atmosphere 1976 is adopted. The 5 × 5 arc-min global elevation data from the ETOPO5 are used to generate the global elevation model coeﬃcients. These coeﬃcients (which represent the geometry of the lower bound of atmospheric masses) are utilized to compute the atmospheric eﬀects with a spectral resolution complete to degree and order 180. The atmospheric eﬀects on gravity disturbances, gravity anomalies and geoid undulations are evaluated globally on a 1 × 1 arc-deg grid.